Figurative Language in Joel Osteen’s Speech “Your Words Become Your Reality” - Theresia Hutagalung; Muhammad Yusuf (LingPoet: Journal of Linguistics and Literary Research, 2022)
This study attempts to explore figurative language in Joel Osteen's speech. This study employed a qualitative approach. The data of this research were from the utterances that occurred in the speech from the speech of Joel Osteen entitled "Your Words Become Your Reality". It was found that from 30 data in the speech, there are 9 simile forms, 5 metaphor forms, 4 personification forms, 2 irony forms, 3 hyperbole forms, 3 litotes forms, 2 metonymy forms, and 2 synecdoche forms. Then, the results of the meaning analysis found 9 denotative meanings and 21 connotative meanings. In addition, the simile is the most frequently used by the speaker in his speech. The figurative function in this speech is used to make the listener's imagination and attract the listener's attention